2002
DOI: 10.1055/s-2002-32070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Integrase by Galloyl Glucoses from Terminalia chebula and Flavonol Glycoside Gallates from Euphorbia pekinensis

Abstract: The bioassay-directed isolation of Terminalia chebula fruits afforded four human immunodeficiency virus type 1 (HIV-1) integrase inhibitors, gallic acid ( 1) and three galloyl glucoses ( 2 - 4). In addition, four flavonol glycoside gallates ( 5 - 8) from Euphorbia pekinensis containing the galloyl moiety also showed the inhibitory activity at a level comparable to those of 2 - 4. By comparison with the activities of the compounds not bearing this moiety, it is proposed that the galloyl moiety plays a major rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 3 publications
1
78
0
Order By: Relevance
“…A number of in vitro and in vivo studies have previously shown that PGG exhibits a wide range of biological activities [41], including anti-inflammatory [16], antioxidant [29], anti-angiogenic [25], antitumor [14], antibacterial activity [40], and a broad range of antiviral activity against respiratory syncytial virus (RSV) [39], Hepatitis B virus (HBV) [18] and Herpes simplex virus (HSV) [27][28]31]. Moreover, it has been shown to have an inhibitory effect on viral enzymes such as integrase and reverse transcriptase of human immunodeficiency virus (HIV-1) [1], and NS3 protease of Hepatitis C Virus (HCV) [9]. Although the underlying mechanisms of its antiviral action remains to be fully elucidated, the wide spectrum of its antiviral activity against different viruses suggests that PGG may target common critical steps in virus-cell interaction rather than a specific viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…A number of in vitro and in vivo studies have previously shown that PGG exhibits a wide range of biological activities [41], including anti-inflammatory [16], antioxidant [29], anti-angiogenic [25], antitumor [14], antibacterial activity [40], and a broad range of antiviral activity against respiratory syncytial virus (RSV) [39], Hepatitis B virus (HBV) [18] and Herpes simplex virus (HSV) [27][28]31]. Moreover, it has been shown to have an inhibitory effect on viral enzymes such as integrase and reverse transcriptase of human immunodeficiency virus (HIV-1) [1], and NS3 protease of Hepatitis C Virus (HCV) [9]. Although the underlying mechanisms of its antiviral action remains to be fully elucidated, the wide spectrum of its antiviral activity against different viruses suggests that PGG may target common critical steps in virus-cell interaction rather than a specific viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Glycyrrhiza uralensis has detoxification, antiulcer, antiinflammation, antiviral, antiatherogenic, and anticarcinogenic effects, 16) and Euphorbia pekinensis has for antiviral and cytotoxic activities. 17,18) Recently, KIOM-79 has suggested possible anti-inflammatory properties by blocking NFkB/Rel and p38 kinase activation. 19) We have investigated the protective effects of KIOM-79 on oxidative stress induced by STZ in this study of the pancreatic b-cells and the likely cytoprotective mechanism.…”
mentioning
confidence: 99%
“…There were no clinically significant adverse events, either reported or observed, during the entire study period. The components of the formulation Amrita Guggulu is having potent anti-inflammatory 19,20 , analgesic, antipyretic 35 , antiarthritic activity 32 , anti-mutagenic/anti-carcinogenic 28 , hypolipidaemic and hypocholesterolemic activities 33,34 hepatoprotective 21,22 , radio protective 23,24 , anti-atherosclerotic 25,26 , antiviral 27 , antioxidant 29,30 , and adaptogenic 31 properties, which are constitutive qualities for any drug to act against hyper-uricaemia induced inflammation. These activities might be mediated by inhibiting TNF-α, IL-1β, IL-8, and NF-κB p65 protein expression in synovial fluid and synovial tissue, and the suppression of NF-κB might be responsible for the decrease of the levels of IL-6, IL-8, and TNF-α in synovial tissue.…”
Section: Discussionmentioning
confidence: 99%